Detection of a Putative TetR-Like Gene Related to Mycobacterium bovis BCG Growth in Cholesterol Using a gfp-Transposon Mutagenesis System - Otal, Isabel; Pérez-Herrán, Esther; Garcia-Morales, Lazaro; Menéndez, María C.; Gonzalez-y-Merchand, Jorge A.; Martín, Carlos; García, María J. (Frontiers in Microbiology, 2017)
In vitro transposition is a powerful genetic tool for identifying mycobacterial virulence genes and studying virulence factors in relation to the host. Transposon shuttle mutagenesis is a method for constructing stable insertions in the genome of different microorganisms including mycobacteria. Using an IS1096 derivative, we have constructed the Tngfp, a transposon containing a promoterless green fluorescent protein (gfp) gene. This transposon was able to transpose randomly in Mycobacterium bovis BCG. Bacteria with a single copy of the gfp gene per chromosome from an M. bovis BCG::Tngfp library were analyzed and cells exhibiting high levels of flourescence were detected by flow cytometry. Application of this approach allowed for the selection of a mutant, BCG_2177c::Tngfp (BCG-Tn), on the basis of high level of long-standing fluorescence at stationary phase. This BCG-Tn mutant showed some particular phenotypic features compared to the wild type strain, mainly during stationary phase, when cholesterol was used as a sole carbon source, thus supporting the relationships of the targeted gene with the regulation of cholesterol metabolism in this bacteria. This approach showed that Tngfp is a potentially useful tool for studying the involvement of the targeted loci in metabolic pathways of mycobacteria.